Integración económica en América Latina: la visión teórica de la CEPAL confrontada con la evolución del proyecto en la región - Vázquez López, Raúl (2011)
This article tracks the main ECLAC ideas over the economic integration in Latin American underlying the change of the ideological background of ECLAC towards an orthodox sense during the nineties. When comparing those ideas with the evolution of intraregional trade in recent years, empirical evidence shows that elements that have historically hindered the projected progress are still present but in more complex forms related to the current dynamics of the international economy. In particular, the implicit management of a partial integration by transnational companies has resulted in unequal relationships between countries and in a wider use from the mentioned process by the strongest economies. The article ends, then, seeking to revitalize the pioneer ideas of ECLAC and proposes guidelines for the construction of an alternative integrationist project that supports the need of exceeding the purely commercial aspects of integration.